Pengaruh Determinan Keputusan Pembelian Skincare Wardah di Shopee: Peran Produk, Review Konsumen, dan Promosi pada Mahasiswa Universitas Indo Global Mandiri Palembang - Putri Putri; Hamid Halin; Siti Komariah Hildayanti (Journal of Indonesian Economic Research, 2026)
The growth of the digital economy and the increasing use of e-commerce platforms have significantly changed consumer purchasing behavior, particularly in the skincare industry. This study aims to analyze the influence of product, consumer review, and promotion on the purchase decision of Wardah skincare through the Shopee platform, with a case study on students of Universitas Indo Global Mandiri (UIGM) Palembang. This research employs a quantitative approach with multiple linear regression analysis using SPSS v.27. Data were collected from 94 respondents through online questionnaires based on purposive sampling. The results show that product has a positive and significant influence on purchase decision (t=3.575, sig.=0.001), consumer review has no significant influence (t=1.527, sig.=0.130), and promotion has a positive and significant influence (t=2.602, sig.=0.011). Simultaneously, all three variables significantly influence purchase decision (F=95.166, sig.=0.000) with an Adjusted R² of 75.2%. These findings support the Theory of Planned Behavior (TPB) framework, in which product forms attitude, consumer review shapes subjective norms, and promotion enhances perceived behavioral control.